Assessment of land cover change in north eastern Nigeria 1986 to 2005 - Garba, Samuel; Brewer, Timothy R. (Canadian Center of Science and Education, 2013)
Environmental disturbance such as drought, overgrazing, and increase in population in north eastern Nigeriaover the years has led to degradation, shortage of land and water resources and sometimes violent conflict amongcommunities. Land cover change provides a vital means of understanding and managing these problems. Thusthis research provided an assessment of how tree, shrub grass, bare ground and urban land cover changed from1986 to 2005. NigeriaSat-1 and Landsat images were used with data obtained from field survey for the landcover classifications. Change in the land covers were analysed according to persistence, swapping, net loss andgain. Uncertainties were analysed by confusion matrices. The overall accuracies of the classifications used forthe analysis are between 60% and 75%. The transition and change accuracies are between 45% and 60%.Approximately 60% of the area of study remained unchanged during the period. Of the remainder,approximately 11% of the area interchanged between shrub grass and bare ground. The most unstable categorywas shrub grass and was also the source of misclassification. The changes in general concurred with theperception of change in the area and gave some insight on the change that occurred.